Bioethanol Production from Musambi Peel by Acid Catalyzed Steam Pretreatment and Enzymatic Saccharification: Optimization of Delignification Using Taguchi Design - John, I. (2019)
Abstract: Citrus waste is an attractive feedstock for second generation bioethanol due to its richness in carbohydrates. For the production of bioethanol, removal of lignin through pretreatment to liberate more cellulose with minimal loss is essential. In the present work, the removal of lignin from musambi (Citrus limetta) peel by acid-catalyzed steam pretreatment and the characterization of musambi peel before and after pretreatment was studied. A Taguchi design was used to optimize solid loading, sulphuric acid concentration and time, for steam pretreatment with delignification as the response. The optimum conditions of process variables were 17 (w/v) for solid loading, 0.25 (v/v) for acid concentration with a time of exposure of 60Â min with maximum delignification of 65. The decrease in peak intensity in FTIR spectra and increase in the crystallinity index of pretreated peel indicated the reduction in pectin, hemicellulose, and lignin. The scanning electron micrographs of pretreated peel clearly showed the delignified microfibrils of cellulose. Enzymatic saccharification of pretreated musambi peel and the effect of peel loading, temperature, time, pH and the loading of cellulase, beta-glucosidase, and pectinase on reducing sugar were also investigated. The maximum reducing sugar obtained after the enzymatic hydrolysis was 386Â mg/g for steam pretreated musambi peel at the optimum conditions whereas it was only 258Â mg/g for the raw musambi peel. Thus, steam pretreatment of musambi peel resulted in better hydrolysis than untreated musambi peel. The yield of bioethanol production at the end of 48Â h of fermentation was 85.97. Â© 2019, Springer Nature B.V.